THE EFFECT OF MACERATION TIME ON TOTAL ALKALOID LEVELS IN BROCOLI (Brassica oleracea var. italica) BY USING UV-Vis SPECTROPHOTOMETRY METHOD - Eni Kartika Sari; Siti Maimunah; Mega Karina Putri (Jurnal Jamu Kusuma, 2022)
ABSTRACT Broccoli is known to be very rich in secondary metabolites, such as alkaloids, flavonoids, tannins, polyphenols, essential oils, and polypeptides. Alkaloids are one of the secondary metabolites that are commonly found in nature and have physiological activities. The extraction time factor is the thing that can affect the quality of the extraction results which in this study is the alkaloid content. This study aims to determine the optimal maceration time so that it can produce optimum total alkaloid content. The stages in this study include sample preparation and then sample extraction by maceration using 96% ethanol with differences in maceration time of 1 day, 2 days and 3 days. Furthermore, identification using TLC and analysis of total alkaloid content using UV-Vis spectrophotometer. Kruskal Wallis test was used to determine whether there was an effect of maceration time on total alkaloid content. The results showed that the highest average total alkaloid content in the second sample was maceration for 2 days with a concentration of 17.5%. The Kruskal Wallis test showed that there was no effect between maceration time on total alkaloid content.